Kebijakan Hukum Pidana dalam Tindakan, Nilai-Nilai Keadilan, dan Kepastian Hukum - Syarifuddin, Syarifuddin (Universitas Medan Area, 2024)
In principle, there is no discriminatory application of law unless law enforcement agencies or organizations individually apply the law discriminatively in social reality. This is because criminal prosecution does not reflect the sense of justice and legal certainty of society. In criminal law policy, it must be linked to the formulation of the principle of formal legality, the principle of certainty, the principle of temporary legitimacy, or the principle of non-retroactivity. The main purpose of law as a theory is to answer the question: What is law and how is it created? Regarding this theory, it is understood as a pure legal theory, namely as a body of law. In the discussion of this paper, the fundamental issues are discussed using a legal-normative approach, supported by the use of a comparative legal approach. Therefore, this research is an analytical descriptive research that uses secondary data sources such as library materials. The data obtained is analyzed qualitatively using descriptive and prescriptive analysis.